Occupational exposures and the risk of COPD: dusty trades revisited. Issue 1 (4th August 2008) - Blanc, P D; Iribarren, C; Trupin, L; Earnest, G; Katz, P P; Balmes, J; Sidney, S; Eisner, M D
Abstract : Background: The contribution of occupational exposures to chronic obstructive pulmonary disease (COPD) and, in particular, their potential interaction with cigarette smoking remains underappreciated. Methods: Data from the FLOW study of 1202 subjects with COPD (of which 742 had disease classified as stage II or above by Global Obstructive Lung Disease (GOLD) criteria) and 302 referent subjects matched by age, sex and race recruited from a large managed care organisation were analysed. Occupational exposures were assessed using two methods: self-reported exposure to vapours, gas, dust or fumes on the longest held job (VGDF) and a job exposure matrix (JEM) for probability of exposure based on occupation. Multivariate analysis was used to control for age, sex, race and smoking history. The odds ratio (OR) and adjusted population attributable fraction (PAF) associated with occupational exposure were calculated. Results: VGDF exposure was associated with an increased risk of COPD (OR 2.11; 95% CI 1.59 to 2.82) and a PAF of 31% (95% CI 22% to 39%). The risk associated with high probability of workplace exposure by JEM was similar (OR 2.27; 95% CI 1.46 to 3.52), although the PAF was lower (13%; 95% CI 8% to 18%). These estimates were not substantively different when the analysis was limited to COPD GOLD stage II or above. Joint exposure to both smoking and occupational factors markedly increased the risk of COPD (OR 14.1; 95% CI 9.33 to 21.2). Conclusions: Workplace exposures are strongly associated with an increased risk of COPD. On a population level, prevention of both smoking and occupational exposure, and especially both together, is needed to prevent the global burden of disease.